Social and psychological consequences of radiological misconceptions following the Fukushima disaster - Morris, Ashley, author; Johnson, Thomas., advisor; Gardner, Danielle, committee member (Colorado State University. Libraries, 2026)
Numerous studies have been conducted regarding the somatic effects of radiation, but the social and psychological impacts remain less studied. The societal and psychological impacts on the residents and evacuees following the tsunami caused by the Great East Japan Earthquake and resulting explosion involving the Fukushima Dai-ichi reactors is seldom emphasized in non-scientific literature. No somatic effects of radiation from the accident have been reported, but communication regarding this has not been effectively disseminated to the public. Radiation can be dangerous, but there are known parameters which must be exceeded to express cellular damage, as well as regulatory limits, shielding and proximity. Additionally, non-scientific media tend to exaggerate radiation dose effects, even when radiation doses are indistinguishable from natural background radiation levels. However, the social and psychological effects of radiation in Japan after this accident have lasted into the present day. Social effects can include ostracization and discrimination from the general populus as well as the individual. Psychological effects tend to be rooted in mental health disorders, extreme fear of radiation, and other, less visible conditions. Research indicates both psychological distress following the incident and a harmful misunderstanding of radiation stemming from the belief that individuals exposed to radiation are radioactive, damaged, or infectious. Psychological and social effects have been measured through the use of surveys of the general populus, as well as interviews, focus groups, and longitudinal studies including those directly affected. Contrary to popular belief, the somatic effects of radiation from this incident are non-existent compared to the social effects that remain to this day. Exposure to radiation and the resultant evacuation changed Fukushima Prefecture lives forever. The majority of lingering effects stem from scientifically unsubstantiated fears regarding radiation, and the evacuation itself, impacting individuals and communities.
Keywords: Japan; radiation; Fukushima; radiophobia; discrimination; prejudice; stigma